2022
DOI: 10.3389/fmicb.2022.1003039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanism of aflatoxin degradation by a novel strain of Trichoderma reesei CGMCC3.5218

Abstract: Aflatoxins, which are produced mainly by Aspergillus flavus and A. parasiticus, are recognized as the most toxic mycotoxins, which are strongly carcinogenic and pose a serious threat to human and animal health. Therefore, strategies to degrade or eliminate aflatoxins in agro-products are urgently needed. We investigated 65 Trichoderma isolates belonging to 23 species for their aflatoxin B1 (AFB1)-degrading capabilities. Trichoderma reesei CGMCC3.5218 had the best performance, and degraded 100% of 50 ng/kg AFB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Samuel et al [ 37 ] also reported that the percentage of AFB 1 degradation by culture supernatant of Pseudomonas aeruginosa N17-1 was elevated from 45% at 20 °C to 90% at 65 °C. The culture supernatant of Trichoderma reesei CGMCC3.5218 could achieve more than 90% AFB 1 degradation at a temperature range from 45 °C to 90 °C [ 38 ]. These results imply that the enzymes or proteins involved in the AFB 1 degradation are thermostable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samuel et al [ 37 ] also reported that the percentage of AFB 1 degradation by culture supernatant of Pseudomonas aeruginosa N17-1 was elevated from 45% at 20 °C to 90% at 65 °C. The culture supernatant of Trichoderma reesei CGMCC3.5218 could achieve more than 90% AFB 1 degradation at a temperature range from 45 °C to 90 °C [ 38 ]. These results imply that the enzymes or proteins involved in the AFB 1 degradation are thermostable.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of Zn 2+ was commonly observed on AFB 1 -degrading strains including Stenotrophomonas sp. CW117 [ 33 ], P. aeruginosa N17-1 [ 37 ] and T. reesei CGMCC3.5218 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant of the isolated strain was mixed with proteinase K at 5 mg/mL or a combination of 5 mg/mL proteinase K and 0.01 mg/mL SDS and then incubated at 37 °C for 10 h. The supernatant of the isolated strain was sterilized at 121 °C. 23 To assess the removal of AFB 1 , these groups were cultured at 37 °C for 12 h.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These fungi can produce various antifungal substances, such as harzianic acid, which act as effective antibiotics against different pathogenic fungi, such as Pythium irregulare , Rhizoctonia solani , and Sclerotinia sclerotiorum [ 26 ]. A recent study [ 27 ] tested 65 isolates of Trichoderma that belong to about 23 species for their AFB1-degrading potentials in a broth medium. Trichoderma reesei CGMCC3.5218 presented the best degrading capacity recording 50 ng kg −1 AFB1 within 3 days (100%) and 10 μg kg −1 AFB1 within 5 days (87.6%).…”
Section: Introductionmentioning
confidence: 99%